QUESTIONS TO INCREASE SECURITY SYSTEMS WATER AND GAS - , І. О. (Municipal economy of cities (Technical science), 2013)
The problems of security of water and gas. Adapts method of constructing mathematical models to calculate the functional reliability engineering services to the question of improving the safety of water and gas.